Functional Movement Is Negatively Associated with Weight Status and Positively Associated with Physical Activity in British Primary School Children - Michael J. Duncan; Michelle Stanley (Journal of Obesity)
Although prior studies have suggested that overweight and obesity in childhood are associated with poorer functional movement performance, no study appears to have examined this issue in a pediatric population. The relations between BMI, ambulatory physical activity and functional movement screen (FMS) performance were compared in 58, 10-11-year-old children. Total FMS score was significantly, negatively correlated with BMI (𝑃=.0001) and positively related to PA (𝑃=.029). Normal weight children scored significantly better for total FMS score compared to children classified as overweight/obese (𝑃=.0001). Mean ± S.D. of FMS scores were 15.5±2.2 and 10.6±2.1 in normal weight and overweight/obese children, respectively. BMI and PA were also significant predictors of functional movement (𝑃=.0001, Adjusted 𝑅2=.602) with BMI and PA predicting 52.9% and 7.3% of the variance in total FMS score, respectively. The results of this study highlight that ambulatory physical activity and weight status are significant predictors of functional movement in British children. Scientists and practitioners therefore need to consider interventions which develop functional movement skills alongside physical activity and weight management strategies in children in order to reduce the risks of orthopaedic abnormality arising from suboptimal movement patterns in later life.